Plants vs. Zombies. Volume 14, A little problem - Tobin, Paul, 1965- (Dark Horse Books, 2019)
"Dr. Zomboss creates an army of teeny zombies to try and sneak up on all the brains in Neighborville! To battle these miniscule menaces, the plants, Crazy Dave, Patrice, and Nate must shrink themselves to have any chance at defeating the zombies. But how will Neighborville's insects react to the invasion of their turf-of-the-tiny? And will this miniature zombie invasion mean the party for Crazy Dave's two-hundred-year-old pants gets cancelled?"--Back cover.